Development of Jejunojejunal Intussusception during Induction Therapy in a Boy with Acute Lymphoblastic Leukemia - NAKAZAWA, Shinpei; SATO, Hiroki; INUKAI, Takeshi; SUGITA, Kanji; UNO, Kanako; NEMOTO, Atsushi; HIROSE, Kinuko; AKAHANE, Koshi; TAKAHASHI, Kazuya; GOI, Kumiko (The Japanese Journal of Pediatric Hematology, 2007)
We report here a 14-year-old boy with acute lymphoblastic leukemia (ALL) who developed intussusception during induction therapy. He was admitted due to fever and anemia, and his white blood cell count was 16, 600/μl with 68% blasts. He was diagnosed as having B-precursor ALL, and his peripheral leukemic blasts disappeared after 1-week oral administration of prednisolone (PSL). After the third administration of vincristine (VCR), he complained of abdominal pain and thereafter a diagnosis of jejunojejunal intussusception was made by abdominal CT scan. Induction chemotherapy was immediately discontinued, and he was kept fasted under intravenous hyperalimentation and administration of antibiotics, H2-blocker, and gabexate mesilate. Surgical treatment was not performed because of bone marrow suppression, severe coagulopathy due to administration of L-asparaginase, and underlying impaired wound healing due to administration of PSL. Abdominal pain gradually subsided and spontaneous remission of intussusception was confirmed by CT scan at day 11 after the onset. Subsequent intestinal contrast X-ray failed to identify any organic lesions possibly leading to intussusception. In the present case, impaired peristaltic movement of the intestine induced by VCR might play a central role in the development of intussusception, in which some minute lesions were possibly implicated as an apex.